Does host-guest interaction promote tolerance behavior? The mediating role of place attachment and subjective well-being - Yajun Jiang; Longfang Huang; Huiling Zhou; Ke Wu (PLoS ONE, 2025)
This study explores the mediating role of place attachment (PA) and subjective well-being (SWB) in the mechanism of tourist tolerance behavior (TTB) from the perspective of host-guest interaction (HGI). Taking the Two Rivers and Four Lakes Scenic Area and Xingping Ancient Town in Guilin, a world-renowned tourist destination in China, as research cases, this study collected survey questionnaires from tourists in the scenic spots and used structural equation modeling to test the theoretical hypotheses of TTB. The results show that HGI has a significantly positive effect on TTB. Tourists’ PA and SWB play a partial mediating role between HGI and TTB. In addition, the study further verified the role of PA and SWB as chain mediators between HGI and TTB. This study not only expands the research scope of tourist citizenship behavior, but also reveals the key factors to improve TTB in tourist destinations. Finally, it provides relevant insights from the perspective of tourist destination management and services.